Historical trends in Hg, Pb and Zn sedimentation in the central shelf area of Portugal - Mil-homens, M.; Branco, V.; Vale, C.; Stevens, R.; Boer, W.; Lebreiro, S.; Cato, I.; Abrantes, F. (Journal of Iberian Geology, 2008)
Temporal records of excess 210Pb, and the determination of major (Al and Ca) and trace elements (Zn, Cr, Ni, Pb, Cu and Hg) in two sediment box-cores, collected in the central area of the Portuguese shelf of North of the Nazaré canyon (offshore from the Lis River), allow evaluation of the deposition of various chemical elements normally associated with anthropogenic activities. In order to compensate for the natural sediment variability, heavy metal contents were normalised to Al. Temporal variations of Hg, Pb and Zn (Al-normalised) show an increasing trend since the beginning of the 1920’s, recording the development of industrial activities. Enrichment factors (EF) were calculated to estimate the level of contamination in these sediments. Mercury is the element with the highest average EF values (EF = 3), followed by Pb (EF = 1.5) and Zn (EF = 1.2). The results indicate that since 1991 64% of total Hg, 44% of total Pb and 24% of total Zn are derived from anthropogenic sources. The average anthropogenic fluxes of Hg, Pb and Zn (0.008, 3, 6 μg cm-2yr-1, respectively) for the last 40 years in a ca. 400 km2 deposition area represent a total accumulation of approximately 30, 12000 and 24400 kg per year of Hg, Pb and Zn, respectively. These results indicate that despite the high-energy conditions and the generally sandy nature of the Portuguese shelf sediments, it is possible to identify significant anthropogenic enrichments in some areas of sediment accumulation. These contaminants are not necessarily related to immediate sources but may instead indicate atmospheric and or marine transport from more distant sources.